A case of hepatic and bone marrow sarcoidosis with progressive renal failure: diagnostic and therapeutic challenges - Brugnaro, Pierluigi; Cattelan, Francesca; Morelli, Erika; Petrucci, Andrea; Marocco, Alessandro; Panese, Sandro; Donisi, Pietro Maria; Capitanio, Giovanni; Tollot, Mauro (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Sarcoidosis is a systemic granulomatous disease, sometimes characterized by an extrapulmonary localization in 30 – 50% of cases. We describe a 60-year-old Italian man with an unexplained history of fatigue, ascitis and progressive renal function impairment. Diagnosis of hepatic and bone marrow sarcoidosis was established by histology, and fast improvement of renal function was obtained after starting  corticosteroid therapy. Atypical presentation and simultaneous involvement of liver, bone marrow and kidneys make diagnosis of extrapulmonary sarcoidosis still a diagnostic challenge. Delayed diagnosis could lead to serious organ damage like a progressive severe kidney failure.